Strategic Marketing Drivers of Air Conditioner Marketing Performance: Role of Competitive Advantage and Technological Turbulence - Bambang Suwarno; Jamaluddin Jamaluddin (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines how strategic marketing drivers influence perceived marketing performance in the air conditioner industry and highlights the roles of competitive advantage and technological turbulence in an emerging-market context. Methodology: This study used a quantitative explanatory approach and analyzed data from 398 air conditioner consumers in Medan City, Indonesia, using SmartPLS. Results: Product differentiation strongly and significantly strengthens competitive advantage, and pricing strategies significantly improve perceived marketing performance. Perceived marketing capabilities also enhance competitive advantage, although they shape performance primarily through indirect pathways. Electronic word?of?mouth, brand reputation, competitive advantage, and technological turbulence do not significantly predict perceived marketing performance directly. These statistically non-significant paths clarify important boundary conditions: middle-income urban consumers who purchase durable goods, such as air conditioners, pay more attention to functional product attributes and value-for-money considerations than to reputational signals, online buzz, or environmental turbulence when they evaluate marketing success. Conclusions: The findings indicate that, in the air conditioner market in emerging urban settings, firms that emphasize product uniqueness and value-based pricing achieve superior perceived marketing performance, while reputational, e-WOM-related, and turbulence-related factors play more selective and context-dependent roles. Limitations: This study focuses on Medan City and perceived marketing performance, which narrows the generalizability of the findings to other regions, segments, and industries. Contributions: This study advances the strategic marketing literature by presenting an integrated model that identifies which strategic marketing drivers most effectively build competitive advantage and perceived marketing performance and by demonstrating when widely cited drivers exert weaker direct effects.